2020
DOI: 10.1002/apj.2439
|View full text |Cite
|
Sign up to set email alerts
|

Ceria‐modified Al‐Mn‐pillared clay catalysts for the selective catalytic reduction of NO with NH3 at low temperatures

Abstract: The yCe/Al-Mn-pillared interlayered clay (PILC, y [Ce content] = 8-9 wt%) catalysts were prepared using the impregnation method. Catalytic activities of the materials for the selective catalytic reduction (SCR) of NO with NH 3 at low temperatures were evaluated, and physicochemical properties of the samples were characterized by X-ray diffraction, N 2 adsorption-desorption, temperature-programmed reduction, ammonia temperature-programmed desorption, X-ray photoelectron spectroscopy, and in situ diffuse reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Figure 2 shows their diffraction patterns. According to our previous research [ 13 ], the XRD pattern of the PILC sample displayed a high-intensity basement (001) reflection peak at 2 θ = 9.3°, indicating that the montmorillonite clay possessed a regular and ordered interlayer structure. The (001) reflection peak of the 3Mo4Ce/Zr-PILC and Pb-poisoned 3Mo4Ce/Zr-PILC catalysts was shifted to a lower angle and its intensity decreased, indicating an increase in interlayer distance and a disorder in the structure of the clay, which was caused by the effect of the strong delamination when the metal oxide entered the interlayer of clay.…”
Section: Resultsmentioning
confidence: 67%
“…Figure 2 shows their diffraction patterns. According to our previous research [ 13 ], the XRD pattern of the PILC sample displayed a high-intensity basement (001) reflection peak at 2 θ = 9.3°, indicating that the montmorillonite clay possessed a regular and ordered interlayer structure. The (001) reflection peak of the 3Mo4Ce/Zr-PILC and Pb-poisoned 3Mo4Ce/Zr-PILC catalysts was shifted to a lower angle and its intensity decreased, indicating an increase in interlayer distance and a disorder in the structure of the clay, which was caused by the effect of the strong delamination when the metal oxide entered the interlayer of clay.…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, the Mn 2p 3/2 signal of each catalyst could be deconvoluted into three components at binding energy (BE)=643.5–644.7, 641.7–642.9, and 640.5–641.7 eV, which were attributed to the surface Mn 4+ , Mn 3+ , and Mn 2+ species, [30–32] respectively. As reported previously, the Mn 4+ species were more active for the low‐temperature SCR reaction [30] . Molar ratios of Mn 4+ /(Mn 2+ +Mn 3+ +Mn 4+ ) on the sample surface were calculated, as summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As reported previously, the Mn 4 + species were more active for the low-temperature SCR reaction. [30] Molar ratios of Mn 4 + /(Mn 2 + + Mn 3 + + Mn 4 + ) on the sample surface were calculated, as summarized in Table 2. Mn 4 + /(Mn 2 + + Mn 3 + + Mn 4 + ) molar ratio decreased in the order of 2Co-4Mn/Fe-PILC (18.9 %) > 2Co-4Mn/Fe-PILC-Pb (16.2 %) > 4Mn/Fe-PILC (14.5 %) > 4Mn/Fe-PILC-Pb (10.3 %).…”
Section: Xps Characterizationmentioning
confidence: 99%
“…Figure 6B shows O 1s XPS spectra of the 4Mn/Fe-PILC and 4Ce-4Mn/Fe-PILC samples before and after SO 2 poisoning. O 1s XPS spectrum of each sample could be divided into three components: The rst component in the BE range of 528.9−529.7 eV corresponded to the surface lattice oxygen (O α ) species, the second one in the BE range of 530.8−531.8 eV was ascribed to the surface chemisorbed oxygen (O β ) species, and the third one in the BE range of 529.7−532.7 eV was attributed to the surface lattice oxygen (O γ ) species of the Si−O bonds in SiO 2 of montmorillonite clay [19,30]. It is well known that the surface chemisorbed oxygen (O β ) species was bene cial for NO removal in the NH 3 -SCR reaction [31].…”
Section: Surface Propertymentioning
confidence: 99%
“…Since Yang and coworkers [17] rst used pillared interlayered clay (PILC) as the low-temperature SCR catalyst in 1992, there have been more and more reports on the PILC-based catalysts. For example, Shen et al [18] found that MnO x /TiO 2 pillared montmorillonite exhibited high NH 3 -SCR activity after doping with a suitable amount of ceria; Cheng et al [19] claimed that the ceriamodi ed Mn-Al-pillared montmorillonite catalyst showed better performance than the commercial catalyst.…”
Section: Introductionmentioning
confidence: 99%